Genetically modified food - PAPPAS (Φ. ΠΑΠΠΑΣ), F.; STEFANIDOU (Μ. ΣΤΕΦΑΝΙΔΟΥ), M. (Journal of the Hellenic Veterinary Medical Society, 2017)
International consensus has been reached on the principles regarding evaluation of the food safety of genetically modified plants. The concept of substantial equivalence has been developed as part of a safety evaluation framework, based on the idea that existing foods can serve as a basis for comparing the properties of genetically modified foods with the appropriate counterpart. Substantial equivalence is a starting point in the safety evaluation, rather than an endpoint of the assessment. The development and validation of new profiling methods, such as DNA microarray technology, proteomics and metabonomics for the identification and characterization of unintended effects, which may occur as a result of the genetic modification, is recommended. The assessment of the allergenicity of newly inserted proteins and of marker genes is discussed. Also, the post-marketing surveillance of the foods derived from genetically modified crops is imperative.